Analysis of Trademark Dispute Cases of PT. Gudang Garam and Gudang Baru - Mishael Joshua; Gunardi Lie; Moody Rizqy Syailendra Putra (CV. Rayyan Dwi Bharata, 2023)
This writing aims to discuss trademark disputes between Gudang Garam and Gudang Baru regarding image names and logos. The problem that arises is a dispute over the brand name and image displayed on the new Warehouse product. Indonesian law regulates two ways to deal with Intellectual Property Rights (IPR) issues, either through a judicial process (litigation) or through a process outside the court (non-litigation). Laws relating specifically to intellectual property rights, viz. HaKi. Brand Law No. 20 of 2016, regulates trademark protection. What is studied in this study is related to the settlement of rights in trademark disputes between Gudang Garam and Gudang Baru, and on the other hand with substantive and legal considerations of judges in trademark disputes between Gudang Garam and Gudang Garam. New. The author of this study will examine in detail the trademark dispute between Gudang Garam and Gudang Baru.